2008
DOI: 10.1002/pon.1475
|View full text |Cite
|
Sign up to set email alerts
|

The religiosity/spirituality of Latina breast cancer survivors and influence on health‐related quality of life

Abstract: Objective-The study evaluated the association of religiosity/spirituality (R/S) and health-related quality of life (HRQOL) among Latina breast cancer survivors (BCS) in order to determine whether R/S would be positively correlated with HRQOL and whether R/S would significantly influence HRQOL. Methods-The cross-sectional study utilized self-report data from 117 Latina BCS survivors. R/ S was measured with the Systems of Belief Inventory -15 Revised (SBI-15R) and HRQOL was measured with the Functional Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
97
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 39 publications
16
97
1
3
Order By: Relevance
“…Coping with the challenges of cancer through religion and spirituality has been shown to be common amongst Hispanic/Latina survivors. This trend is consistent with a cultural framework that places high value on religiosity/spirituality 48,49 . Some studies have found that higher levels of religiosity/ spirituality are associated with positive reports of health-related quality of life in young Hispanic/Latina breast cancer survivors 48 .…”
Section: Cultural Factorssupporting
confidence: 65%
See 1 more Smart Citation
“…Coping with the challenges of cancer through religion and spirituality has been shown to be common amongst Hispanic/Latina survivors. This trend is consistent with a cultural framework that places high value on religiosity/spirituality 48,49 . Some studies have found that higher levels of religiosity/ spirituality are associated with positive reports of health-related quality of life in young Hispanic/Latina breast cancer survivors 48 .…”
Section: Cultural Factorssupporting
confidence: 65%
“…This trend is consistent with a cultural framework that places high value on religiosity/spirituality 48,49 . Some studies have found that higher levels of religiosity/ spirituality are associated with positive reports of health-related quality of life in young Hispanic/Latina breast cancer survivors 48 . However, this finding is inconsistent in the literature, and does not focus on quality of life issues specific to body image and sexual functioning 50 .…”
Section: Cultural Factorssupporting
confidence: 65%
“…Because perceived helplessness and lack of self-assurance may inhibit seeking medical care, religious coping may indirectly encourage actual help-seeking behavior by obviating these obstacles to treatment. In a sample of Latina breast cancer patients, a composite measure of spiritual beliefs, practices, and support was linked to greater perceived positivity of one's relationship with one's physician [40]. It seems reasonable to presume that people with positive relationships with their physicians would be more likely to seek medical care and cooperate with the medical advice they receive.…”
Section: Religious Coping and Active Copingmentioning
confidence: 99%
“…Composite measures of public and private religious activities, traditional religious beliefs, and positive religious coping have been positively related to social support in samples with cancer, HIV/AIDS, and heart conditions [7,8,25,40]. In a study of Turkish women with breast cancer, seeking assistance from supernatural forces was related to better social functioning [73].…”
Section: Religious Coping Social Support and Healthmentioning
confidence: 99%
“…For example, religiosity/spirituality (R/S) has been associated with better health-related quality of life (Canada, Murphy, Fitchett, Peterman, & Schover, 2008;Edmondson, Park, Blank, Fenster, & Mills, 2008;Wildes, Miller, de Majors, & Ramirez, 2009) and general mental health (Purnell, Andersen, & Wilmot, 2009), and lower levels of depression (Canada et al, 2008; and traumatic stress in cancer survivors (Purnell et al, 2009). Similarly, reliance on a benevolent relationship with God is associated with better emotional and interpersonal functioning (Agarwal, Hamilton, Crandell, Moore, 2010;Gall, 2004).…”
mentioning
confidence: 99%